Mathematical modeling and Hopf bifurcation analysis of tumor macrophage interaction with polarization delay - Jianping Li; Nan Liu; Danni Wang; Hongli Yang (Journal of Biological Dynamics)
Macrophages have both anti-tumor and pro-tumor effects. Time delay is commonly observed in real systems, yet its impact on tumor-macrophage dynamics remains unclear. This paper develops a new tumor-macrophage model with time delay. The model describes the interactions between tumor cells (T), the classically activated macrophages (M1), the alternatively activated macrophages (M2), and the inactive macrophages (M0). The system's solution is computed, and equilibrium stability is analyzed. The existence of Hopf bifurcation is subsequently established. There exists bifurcating periodic solutions near the internal equilibrium, showing tumor cells and macrophages can coexist in the long term, as well as the potential for tumor relapse. Furthermore, the normal form and center manifold theorem are utilized to study the nature of Hopf bifurcation. Sensitivity analysis highlights the effect of parameters on tumor population dynamics. Numerical simulations validate the theory, elaborating the model can serve as a useful tool for tumor system analysis.